«ՀԱՅԿՕ»՝ Թալէաթի ահաբեկումին վերջին անծանօթ մասնակիցը - Մատթէոսեան, Վարդան («Նաիրի» հրատ.)
In his memoirs published in 1953, Soghomon Tehlirian disclosed the details of the assassination of Talaat Pasha, the mastermind of the Armenian genocide, which he had carried in March 1921. For security reasons, he introduced his immediate collaborators in Berlin with pseudonyms: Hrap, Hazor, Vaza, Haiko. While the name of the first, Hrach Papazian (1892-1960), was already disclosed in Arshavir Shiragian‘s memoirs (1965), the actual identities of Hazor (Hakob Zorian, 1894-1942, a Soviet Armenian historian, victim of the Stalinist purges) and Vaza (Vahan Zakarian, 1883-1980, one of the translators during Tehlirian‘s trial) were revealed two decades later. However, Haiko‘s name has been ignored by most researchers and there has been no attempt to identify him
Keywords: Ահաբեկչություն; Հայոց ցեղասպանություն